Performance of a Newly Isolated Salt-Tolerant Yeast Strain Sterigmatomyces halophilus SSA-1575 for Azo Dye Decolorization and Detoxification - Al-Tohamy, Rania; Kenawy, El-Refaie; Sun, Jianzhong; Ali, Sameh Samir (Frontiers in Microbiology, 2020)
The effective degradation of hazardous contaminants remains an intractable challenge in wastewater processing, especially for the high concentration of salty azo dye wastewater. However, some unique yeast symbionts identified from the termite gut system present an impressive function to deconstruct some aromatic compounds, which imply that they may be valued to work on the dye degradation for various textile effluents. In this investigation, a newly isolated and unique yeast strain, Sterigmatomyces halophilus SSA-1575, was identified from the gut system of a wood-feeding termite (WFT), Reticulitermes chinensis. Under the optimized ambient conditions, the yeast strain SSA-1575 showed a complete decolorization efficiency on Reactive Black 5 (RB5) within 24 h, where this azo dye solution had a concentration of a 50 mg/L RB5. NADH-dichlorophenol indophenol (NADH-DCIP) reductase and lignin peroxidase (LiP) were determined as the key reductase and oxidase of S. halophilus SSA-1575. Enhanced decolorization was recorded when the medium was supplemented with carbon and energy sources, including glucose, ammonium sulfate, and yeast extract. To understand a possible degradation pathway well, UV-Vis spectroscopy, FTIR and Mass Spectrometry analyses were employed to analyze the possible decolorization pathway by SSA-1575. Determination of relatively high NADH-DCIP reductase suggested that the asymmetric cleavage of RB5 azo bond was mainly catalyzed by NADH-DCIP reductase, and finally resulting in the formation of colorless aromatic amines devoid of any chromophores. The ecotoxicology assessment of RB5 after a decolorization processing by SSA-1575, was finally conducted to evaluate the safety of its metabolic intermediates from RB5. The results of Microtox assay indicate a capability of S. halophilus SSA-1575, in the detoxification of the toxic RB5 pollutant. This study revealed the effectiveness of halotolerant yeasts in the eco-friendly remediation of hazardous pollutants and dye wastewater processing for the textile industry.